Pembagian Harta Bersama dalam Perkawinan Poligami Berdasarkan Kompilasi Hukum Islam - Mayva, Verandha; Prihatini, Farida (Wajah Hukum, 2025)
Marriage according to Law Number. 1 of 1974 and the Compilation of Islamic Law (KHI) is based on the principle of monogamy, which allows the practice of polygamy under certain conditions. In polygamous marriages, the division of shared property is regulated by Islamic law and legislation to ensure justice and protect the rights of the parties involved. However, the division of joint property often causes problems due to the lack of clarity in the mechanisms for calculation and proof of ownership. This research aims to analyze the mechanism of joint property division in polygamous marriages based on the KHI, with a primary focus on Decision Number 555/K/AG/2012. The approach used is normative juridical with a qualitative analysis method, referring to the analysis of legislation, namely Law Number 1 of 1974 on Marriage and the KHI. The analysis results show that the division of joint property in polygamous marriages is determined based on the time of acquisition, where property obtained during the marriage with the first wife becomes the joint right of the husband and the first wife. Meanwhile, property acquired in subsequent marriages involves the next wives in its ownership. The case study of Decision Number 555/K/AG/2012 emphasizes the importance of proving the period of asset acquisition to ensure fairness in the distribution.